Esthetic rehabilitation of discolored tooth and gingival hyperpigmentation with external bleaching and gingival ablasion: A case report - Aswar, Aulia A.; Dwiandhany, Wahyuni S.; Nugroho, Juni J.; Hikmah, Noor; Natsir, Nurhayaty; Trilaksana, Aries C. (Journal of Case Reports in Dental Medicine, 2024)
Objective: Dental discoloration accompanied by gingival hyperpigmentation can be found in daily practice, although it is rare. Gingival hyperpigmentation is caused by excessive melanin deposition in the basal and suprabasal   cell   layers   of   the   epithelium. Gingival depigmentation can be removed by electrosurgery, periodontal surgery, and laser ablation.Methods: During the initial appointment, external bleaching with 40% Hydrogen Peroxide bleaching agent (Opalescent Boost, Ultradent) was applied for 20 minutes to the maxillary and mandibular teeth. The change from the initial color number 8 to 4 (Shade Guide Opalescent Boost, Ultradent) was observed. On the next appointment, the patient had laser ablation treatment on hyperpigmented gums.Results: External bleaching can generally be done with hydrogen peroxide (H2O2) to get optimal brightening results.Conclusion: External bleaching for vital teeth using hydrogen peroxide is a conservative technique with satisfactory results, easy to perform, and highly effective for removing tooth discoloration. While gingival ablation is performed to treat gingival hyperpigmentation. After both procedures, better aesthetic results were obtained.